The double deal - Mann, Catherine (Harlequin desire, 2018)
"Naomi Steele knows it's sneaky to sleep with Royce Miller without revealing her true identity. So is neglecting to mention she's pregnant. Still, being stranded with the reclusive scientist provides the perfect opportunity to convince him to work for her family's company. Yet once the snow melts and the truth is revealed, Naomi could be dealing with double the trouble..."-- Page [4] of cover.